(untitled) (Physical Education, Health and Social Sciences, 2026)
The integration of advanced biotechnology into functional food production has revolutionized the development of probiotic-enriched products that deliver targeted health benefits while providing robust biocontrol against foodborne pathogens. This review synthesizes recent progress in metabolic engineering, synthetic biology (including CRISPR/Cas9), precision fermentation, and multi-omics-driven strain selection to create next-generation probiotics (NGPs) with enhanced viability, stress tolerance, and bioactive metabolite production (e.g., bacteriocins, organic acids, SCFAs). Valorization of agro-industrial residues through optimized fermentation further enhances sustainability and nutritional value. Innovative delivery systems microencapsulation (extrusion, emulsion, spray drying), nanotechnology, and 3D food printing ensure high probiotic survival (>10^8 CFU/mL) through processing, storage, and gastrointestinal transit. Probiotic functional foods exert potent antimicrobial effects via multiple mechanisms: production of antimicrobial peptides (e.g., nisin, pediocin), pH reduction, competitive exclusion, and biofilm interference, achieving significant log reductions (2–8 log) against major pathogens including Listeria monocytogenes, Salmonella Typhimurium, Escherichia coli O157:H7, and Staphylococcus aureus across dairy, plant-based, and meat matrices. The review also addresses matrix diversification (dairy, cereal, fruit, vegetable, and fermented meat products), market trends toward personalized and precision nutrition, regulatory frameworks (EFSA QPS, FDA GRAS), and safety considerations. Collectively, these biotechnological advancements position probiotic functional foods as sustainable, multi-functional solutions for improving food safety, gut health, and global nutrition security.